2022
DOI: 10.13075/ijomeh.1896.01829
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of unstimulated salivary flow rate, IgA and clinical oral dryness among active and passive smokers

Abstract: The aim of this study was to assess the impact of smoking on the whole salivary flow rate (SFR), IgA levels and clinical oral dryness (COD) among active and passive smokers. Material and Methods: The participants were categorized as active smokers (N = 54) or passive smokers (N = 163). Saliva was collected in tubes and placed in ice storage at -70°C. Salivary IgA levels were assessed in duplication using the enzyme linked immunosorbent assay (ELISA) method. Following the saliva sample collection, the subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Smokers are exposed to more than 7000 chemicals per puff, which alters the salivary component, resulting in impaired oral protection 6 . Seeme et al 7 showed that active smokers had higher clinical oral dryness (COD) scores and lower salivary flow rate (SFR). Xerostomia, a subjective sensation of dry mouth, is a side effect of e-cigarette use in adults and youth 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Smokers are exposed to more than 7000 chemicals per puff, which alters the salivary component, resulting in impaired oral protection 6 . Seeme et al 7 showed that active smokers had higher clinical oral dryness (COD) scores and lower salivary flow rate (SFR). Xerostomia, a subjective sensation of dry mouth, is a side effect of e-cigarette use in adults and youth 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%